Testing Parameters in GMM without Assuming that they are identified - Frank Kleibergen (Tinbergen Institute, 2001)
We propose a generalized method of moments (GMM) Lagrange multiplier statistic, i.e. the K statistic, that uses a Jacobian estimator based on the continuous updating estimator that is asymptotically uncorrelated with the sample average of the moments. Its asymptotic (...)
Keywords: 330; Weak instruments; Size distortions; Covariance matrix estimators; stochastic discount factors; Statistischer Test; Schätztheorie; Theorie; Momentenmethode